Scots Pine Bark Extracts as Co-Hardeners of Epoxy Resins - Tomasz Szmechtyk (Molecules)
Extracts from natural waste like bark or leaves are great sources of phytochemicals, which contain functional groups (hydroxyl, carboxylic, vinyl, allyl) attractive in terms of polymer synthesis. In this study, the synthesis of epoxy with an extract of Scots pine bark as a natural co-hardener was evaluated. Ultraviolet-visible (UV-Vis) spectroscopy was used for the identification of phytochemicals with conjugated dienes and quantification of TPC. Also, the total solid content (TSC) of representative extracts was calculated. The best extract in terms of total phenolic content (TPC) value was selected as a co-hardener and investigated using differential scanning calorimetry (DSC) for thermal effects and attenuated total reflectance Fourier transform infrared spectroscopy (ATR FTIR) for reactions between functional groups. Also, the mechanical properties (flexural modulus, flexural strength, impact strength, Shore D hardness) and density of composition were obtained for extract-based epoxy and compared to reference sample values. Results were discussed in terms of future research and improvement of compositions. Also, potential applications were proposed.